ANALYSIS OF INDICATORS OF PROFITABILITY OF THE ENTERPRISE: THEORETICAL AND APPLIED ASPECTS - NOVICHENKO, LYDMILA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the conditions of unstable and crisis-driven economic development, the significant negative impact of significant market fluctuations on financial results, the main attention of management personnel is focused on ensuring profit and increasing the company's profitability indicators. The profitability indicators of the enterprise determine the level of its investment attractiveness, competitiveness and continuity of operation. Today, the extensive factors of production growth are becoming more and more limited and their application does not bring the desired economic effect. In this regard, the question of profitability analysis is an important and urgent problem of the theory and practice of enterprise activity. Based on the study of the meaning of the concept of "profitability", the expediency of clarifying the interpretation of its meaning is substantiated. Based on the results of the study, the interpretation of the meaning of the definition "profitability" was clarified and the author's interpretation of its meaning was proposed. In order to improve the theoretical and applied provisions of the analysis of the profitability of the enterprise, an organizational and informational model of the analysis of the profitability of the enterprise was developed. The developed organizational and information model consists of nine interconnected elements, each of which defines processes and phenomena, evaluation indicators and interested subjects of the analysis of the profitability of the enterprise. The consistent implementation of the presented elements of the organizational and information model of the analysis of the company's profitability will ensure the improvement of the organization of analytical work in terms of assessing the efficiency and profitability of the company's activities. In the future, it will also allow optimizing the process of managing profitability indicators to strengthen the financial condition of the business entity and its competitive positions on the market. Based on the analysis of scientific developments in the field of finding sources and methods of increasing the profitability of the enterprise, the ways of increasing the profitability of the enterprise and increasing the efficiency of production have been systematized. The need to take into account cause-and-effect relationships and the results of factor analysis for the development of directions for increasing the level of indicators of the profitability of the enterprise is substantiated.
Keywords: profitability; enterprise efficiency; competitiveness; model; factor analysis; enterprise